A=\(\dfrac{\sqrt{x}}{\sqrt{x}-5}-\dfrac{10\sqrt{x}}{x-25}-\dfrac{5}{\sqrt{x}+5}=\dfrac{\sqrt{x}\left(\sqrt{x}+5\right)-10\sqrt{x}-5\cdot\left(\sqrt{x}-5\right)}{\left(\sqrt{x}+5\right)\cdot\left(\sqrt{x}-5\right)}\)
=\(\dfrac{x+5\sqrt{x}-10\sqrt{x}-5\sqrt{x}+25}{\left(\sqrt{x}+5\right)\left(\sqrt{x}-5\right)}\)=\(\dfrac{x+25}{\left(\sqrt{x}+5\right)\cdot\left(\sqrt{x}-5\right)}\)
=\(\dfrac{\left(\sqrt{x}+5\right)\cdot\left(\sqrt{x}+5\right)}{\left(\sqrt{x}+5\right)\cdot\left(\sqrt{x}-5\right)}=\dfrac{\sqrt{x}+5}{\sqrt{x}-5}\)(1)
2)thay x =9 vào (1) ta được
\(\dfrac{\sqrt{9}+5}{\sqrt{9}-5}\)=\(\dfrac{3+5}{3-5}\)=\(\dfrac{8}{-2}\)=-4
vậy với x=9 thì y=-4